Dampak subsidi kesehatan terhadap konsumsi rokok dan pola konsumsi rumah tangga penerima bantuan iuran - Solida, Adila; Sari, Rumita Ena; Mekarisce, Arnild Augina; Hidayati, Fajrina (Proceedings Academic Universitas Jambi, 2025)
High cigarette consumption rates not only impact public health but are also a factor that exacerbates poverty in Indonesia. It is concerning that in Indonesia, the highest cigarette consumption comes from poor household heads (82%). On the other hand, poor/underprivileged families receive health subsidies from the JKN-PBI program every month. High cigarette consumption also occurs in Jambi City (19.74%), resulting in a decrease in household expenditure allocation for nutritious consumption, especially for low-income families. This study aims to identify the impact of health subsidies on the consumption patterns of PBI households in Jambi City by analyzing the differences in average cigarette consumption, food consumption, and non-food consumption of households receiving premium assistance between before and after receiving JKN-PBI subsidies. Quantitative research based on economic evaluation involved 120 respondents selected using systematic sampling techniques in three Community Health Center (Puskesmas) work areas in Jambi City. The results showed that there were differences in the average costs of food consumption, health costs, and cigarette costs between before and after respondents became JKN-PBI participants. It was concluded that cigarette consumption has an impact on the consumption patterns of PBI participant households. It is recommended that the government and BPJS Kesehatan consider a policy of providing health subsidies to JKN participants who smoke.